An Iterative Algorithm for Solving n-Order Fractional Differential Equation with Mixed Integral and Multipoint Boundary Conditions. (22nd January 2021) - Tan, Jingjing; Zhang, Xinguang; Liu, Lishan; Wu, Yonghong
Abstract : In this paper, we consider the iterative algorithm for a boundary value problem of n -order fractional differential equation with mixed integral and multipoint boundary conditions. Using an iterative technique, we derive an existence result of the uniqueness of the positive solution, then construct the iterative scheme to approximate the positive solution of the equation, and further establish some numerical results on the estimation of the convergence rate and the approximation error.